Application of steel slag in cement treated aggregate base course. (1st October 2020) - Liu, Jinzhou; Yu, Bin; Wang, Qian
Abstract: Steel slag, which can be used as a cementitious material, is widely used in road engineering. However, it is less applied in the base course. The feasibility of the application of steel slag in the road base was examined and the optimal replacement content of aggregate was determined. Different contents of steel slag (30%, 50%, and 70% by volume) were blended into the concrete. The mechanical and durability performance of the mixture were tested. The microstructure and elements distribution were characterized by the scanning electron microscopy (SEM) and the energy dispersive X-ray spectroscopy (EDS). The experiments manifest that steel slag is beneficial for the reinforcement of the strength and shrinkage performance of concrete, making it possible to replace aggregate. The unconfined compressive strength (UCS) change trend at 7d is positively related to cement content. The blend with 50% of steel slag has the maximum strength and stiffness at 4% cement content. In pace with the steel slag amount increases, the freeze resistance and dry shrinkage performance of samples increase, but the temperature shrinkage performance decreases. Besides, the minimum mass losses of samples are those with 50% of steel slag. The microstructure results imply the addition of steel slag increases the amount of hydration products, making the structure tighter and of lower porosity. Molecular simulations also reveal steel slag increases the electrostatic interaction and bonding effect with cement. The addition of steel slag into the road base is feasible, with the best overall performance obtained at the content of 50%. Steel slag mixture has sound economic benefit and potential great environmental benefit compared to limestone mixture. It is worth reminding when steel slag is applied in an engineering project, production process control of steel slag aggregate is required. Highlights: The water absorption of the steel slag is greater than limestone. Best overall performance can be obtained when the replacement content of steel slag is 50%. The content of silica fume in steel slag mixture is preferably 3% to prevent expansion. Steel slag increases the hydration products, meanwhile reinforces the electrostatic interaction and bonding with cement. Steel slag mixture has sound economic benefit and potential great environmental benefit compared to limestone mixture.